Association of low socioeconomic status and limited dental health-care access on poor oral health outcomes among United States adults - Apexa B Patel; Kunj Sanghvi; Sandeep Shelly; Viral Patel (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective was to examine the association of having poor oral health-care access and low socioeconomic status on poor oral health outcomes such as gingivitis/periodontitis and severe periodontitis in United States (US) adults. Methods: A cross-sectional analysis of 4745 US adults 30 years and older from the National Health and Nutrition Examination Survey (NHANES) 2015-2016 was done. Poor oral health outcomes were determined by the response of the respondents to the questionnaire. Logistic and regression analyses were used to determine the association of having poor oral health-care access and low socioeconomic status on poor oral health outcomes. To take into account the complex survey sampling methods, all the analyses were weighted. Results: This research study found an increased association between limited dental health-care access and poor oral health outcomes such as gingivitis/periodontitis and severe periodontitis among US adults aged 30 years and older. The low socioeconomic status and severe periodontitis results of the unadjusted model of the regression analysis suggest that people who belong to the low socioeconomic group were less likely to have severe periodontitis than people who belong to the high socioeconomic group. In all the other regression models, low socioeconomic status did not have a significant association with poor oral health outcomes such as gingivitis/periodontitis and severe periodontitis. Conclusion: On analyzing the NHANES 2015-2016 data, an increased association between limited dental health-care access and poor oral health outcomes such as gingivitis/periodontitis and severe periodontitis was found in US adults aged 30 years and older. A decreased association was found for low socioeconomic status and severe periodontitis from the unadjusted model of the regression analysis. More research is needed to solve the issue of having poor oral health outcomes such as gingivitis and periodontitis due to not having enough access to dental health care among low-income US adults.